Ответы и объяснения

  • AlbuRin
  • светило науки
2013-07-15T09:29:53+00:00

(2x+5)/(4x-3)  =  (3x+3) / (7-x)

ОДЗ      4х-3  не=0,         7-х   не=0

(2x+5)*(7-x)   =   (3x+3)*(4x-3)

14х + 35 -2x^2  -5x  =  12x^2  +  12x  -  9x  -  9

12x^2  +  2x^2  +  3x  -  9x  -  9  -  35  =  0

  14x^2  -  6x  -  44  =  0

7x^2  -  3x  -  22  =  0

D  =  b^2  -  4ac  =  9  +  616  =  625  =  25^2  > 0

x_1  =  (-b  +  VD) / 2a  =  (3  +  25) /14  =  28/14  =  2

x_2  =  (-b  -  VD) / 2a  =  (3  -  25)  / 14 =  -22 / 14  =  -11/7  =  -1 4/7

Овет.      -1 4/7;          2.